Classification and Natural History of the Neuronal Ceroid Lipofuscinoses. (September 2013) - Mink, Jonathan W.; Augustine, Erika F.; Adams, Heather R.; Marshall, Frederick J.; Kwon, Jennifer M.
The neuronal ceroid lipofuscinoses represent a group of disorders characterized by neurodegeneration and intracellular accumulation of an auto-fluorescent lipopigment (ceroid lipofuscin). Together, they represent the most prevalent class of childhood neurodegenerative disease. The neuronal ceroid lipofuscinoses encompass several distinct biological entities that vary in age of onset, specific neurologic phenotype, and rate of progression. In this review, we describe 9 major forms and present a classification scheme. Understanding the age of onset, clinical features, and natural history can inform rational diagnostics. Better knowledge of the natural histories of these disorders is necessary to shed light on the underlying pathobiology and to develop new therapeutics.